Sistem Penilaian Kinerja Tridharma Dosen Menggunakan SAW - Angga Lisdiyanto (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Lecturers are given the obligation to carry out the tridharma of higher education which includes teaching, research, and community service. Then several other tasks suggested to be carried out by all lecturers in Indonesia. In this case the problem that occurs is that there is not yet a system that evaluates the performance of lecturers in implementing the Tridarma of Higher Education. So that it affects the quality in carrying out the tridarma of higher education. The application of this lecturer performance appraisal system can help assess and evaluate lecturer performance by determining each criterion. The SAW method is applied in this study because the SAW method determines the weight of each predetermined criterion. To then proceed in the normalization process using the buying and selling that is in the method. Then proceed with the ranking process to select the best alternative, in this case what is meant is the lecturer who has the best performance from the results of calculating the points for each comparison. The results of this study are in the form of a performance appraisal system application using a web-based simple additive weighting method.